Diabetes mellitus and chronic kidney disease: achievements, unresolved problems, and prospects for therapy - Marina Vladimirovna Shestakova; Minara Shamkhalovna Shamkhalova; Ivona Yanovna Yarek-Martynova; Inna Igorevna Klefortova; Olga Yur'evna Sukhareva; Olga Konstantinovna Vikulova; Natalya Vladislavovna Zaytseva; Sergey Andreevich Martynov; Malkhaz Viktorovich Kvaratskheliya; Evgeny Vladimirovich Tarasov; Natalya Petrovna Trubitsyna (Сахарный диабет)
The dramatic increase in the number of patients with diabetes mellitus (DM) and chronic renal disease (CRD) in the recent years emphasizes the closeassociation between the two conditions and the leading role of DM in the development of renal pathology. Diabetology and nephrology are highly costlybranches of public health, and the burden of substitution renal therapy in DM patients continues to grow. The necessity of a renoprotection programat the early stages of DM for the prevention or delay of terminal renal insufficiency becomes increasingly clear. Such program should be based on theconceptual model of the evolvement of diabetic nephropathy as a consequence of combined action of metabolic and hemodynamic factors modulatedby genetic ones.